Identification and characterization of DEAD-box RNA helicase DDX3 in rainbow trout (Oncorhynchus mykiss) and its relationship with infectious hematopoietic necrosis virus infection. (October 2022) - Zhao, Jing-Zhuang; Xu, Li-Ming; Ren, Guang-Ming; Shao, Yi-Zhi; Lu, Tong-Yan
Abstract: DDX3, a member of the DEAD-box RNA helicase family and has highly conserved ATP-dependent RNA helicase activity, has important roles in RNA metabolism and innate anti-viral immune responses. In this study, five transcript variants of the DDX3 gene were cloned and characterized from rainbow trout ( Oncorhynchus mykiss ). These five transcript variants of DDX3 encoded proteins were 74.2 kDa (686 aa), 76.4 kDa (709 aa), 77.8 kDa (711 aa), 78.0 kDa (718 aa), and 78.8 kDa (729 aa) and the predicted isoelectric points were 6.91, 7.63, 7.63, 7.18, and 7.23, respectively. All rainbow trout DDX3 proteins contained two conserved RecA-like domains that were similar to the DDX3 protein reported in mammals. Phylogenetic analysis showed that the five cloned rainbow trout DDX3 were separate from mammals but clustered with fish, especially Northern pike ( Esox lucius ) and Nile tilapia ( Oreochromis niloticus ). RT-qPCR analysis showed that the DDX3 gene was broadly expressed in all tissues studied. The expression of DDX3 after infectious hematopoietic necrosis virus (IHNV) infection increased gradually after the early stage of IHNV infection, decreased gradually with the proliferation of IHNV in vivo (liver, spleen, and kidney), and was significantly decreased after the in vitro infection of epithelioma papulosum cyprini (EPC) and rainbow trout gonad cell line-2 (RTG-2) cell lines. We also found that rainbow trout DDX3 was significantly increased by a time-dependent mechanism after the poly I:C treatment of EPC and RTG cells; however no significant changes were observed with lipopolysaccharide (LPS) treatment. Knockdown of DDX3 by siRNA showed significantly increased IHNV replication in infected RTG cells. This study suggests that DDX3 has an important role in host defense against IHNV infection and these results may provide new insights into IHNV pathogenesis and antiviral drug research. Highlights: Five transcript variants of DDX3 gene were cloned and characterized from rainbow trout. Rainbow trout DDX3 contains conserved RecA-like domains similar with mammals. Rainbow trout DDX3 was increased at early stage and decreased at late stage during IHNV infection in vivo. DDX3 was increased after poly I:C treatment but decreased after IHNV infection in vitro. Knockdown of DDX3 by siRNA increased IHNV replication in RTG-2 cells.